2021
DOI: 10.3389/fcimb.2021.766922
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Membrane (M) and Spike (S) Proteins Antagonize Host Type I Interferon Response

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread worldwide and has infected more than 250 million people. A typical feature of COVID-19 is the lack of type I interferon (IFN-I)-mediated antiviral immunity in patients. However, the detailed molecular mechanisms by which SARS-CoV-2 evades the IFN-I-mediated antiviral response remain elusive. Here, we performed a comprehensive screening and identified a set of SARS-CoV-2 proteins that antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…Taken together, these data show that Omicron viruses are less effective than Delta viruses in antagonising the interferon response in human cells, which may contribute to the lower pathogenicity of the Omicron variant observed in patients [21,22]. Notably, SARS-CoV-2 proteins known to inhibit the host cell interferon response including S, NSP3, NSP6, NSP14, nucleocapsid (N), and membrane (M) are mutated in the Omicron variant [23,24].…”
Section: Figurementioning
confidence: 99%
“…Taken together, these data show that Omicron viruses are less effective than Delta viruses in antagonising the interferon response in human cells, which may contribute to the lower pathogenicity of the Omicron variant observed in patients [21,22]. Notably, SARS-CoV-2 proteins known to inhibit the host cell interferon response including S, NSP3, NSP6, NSP14, nucleocapsid (N), and membrane (M) are mutated in the Omicron variant [23,24].…”
Section: Figurementioning
confidence: 99%
“…Apart from the earlier 4 proteins, a few additional proteins also inhibited IFN induction (NSP5) or signaling (NSP7, NSP9, ORF9b), though less effectively (Sup Fig 1B). To further substantiate our results, we compiled and compared the data from previous studies where similar reporter-based approaches were utilized to screen for IFN antagonists of SARS-CoV-2 (Fig 1C, D) (Lei et al ., 2020), (Li et al , 2020), (Xia et al ., 2020), (Yuen et al , 2020), (Zhang et al , 2021), (Hayn et al , 2021), (Stukalov et al , 2021), (Shemesh et al , 2021), (Fu et al , 2021). Our findings largely corroborated other studies, and this comparison revealed ORF6 as the most consistent and effective inhibitor of IFN induction and ISG signaling across various studies (Fig 1D) (Lei et al ., 2020), (Li et al ., 2020), (Xia et al ., 2020), (Yuen et al ., 2020), (Zhang et al ., 2021), (Vazquez et al , 2021), (Hayn et al ., 2021), (Stukalov et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…observed that the SARS-CoV-2 M protein did not significantly affect IRF3 phosphorylation, but blocked its nuclear translocation. Likewise, the S protein was found to suppress STAT1 phosphorylation and nuclear translocation by intervening with JAK1-STAT1 interaction ( 56 ). On the other hand, without directly influencing STAT1 and STAT2 activation, nsp7 and ORF7a clearly inhibited ISRE promoter activity ( 56 ).…”
Section: Sars-cov-2 Evolved Strategies To Target Ifn Signalingmentioning
confidence: 99%
“…Likewise, the S protein was found to suppress STAT1 phosphorylation and nuclear translocation by intervening with JAK1-STAT1 interaction ( 56 ). On the other hand, without directly influencing STAT1 and STAT2 activation, nsp7 and ORF7a clearly inhibited ISRE promoter activity ( 56 ). Nsp9 and ORF8 exhibited inhibition of STAT1 activation, whereas Helicase and E protein intervened with STAT1 and STAT2 activation ( 56 ).…”
Section: Sars-cov-2 Evolved Strategies To Target Ifn Signalingmentioning
confidence: 99%